2016
DOI: 10.1186/s13018-016-0395-9
|View full text |Cite
|
Sign up to set email alerts
|

Single minimal incision fasciotomy for chronic exertional compartment syndrome of the lower leg

Abstract: BackgroundChronic exertional compartment syndrome (CECS) involves a painful increase in compartment pressure caused by exercise and relieved by rest, common in athletes. The most common site for CECS in the lower limbs is the anterior leg compartment. The aim of this study is to evaluate the outcomes of a single minimal incision fasciotomy in athletes and their capability to return to high level sport activity.MethodsThe study reports mid-term results in a series of 18 consecutive athletes with chronic exertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
5
26
0
1
Order By: Relevance
“…Patients with CECS who had a fasciotomy were satisfied with the surgical therapy and reported better subjective injury status than conservative-treated patients with ERLP. A success rate of 84.4% for fasciotomy in CECS was reported and is in concordance within the range of 78%–98% reported by other studies 3 7 18–20. The difference between fasciotomy and conservative groups in satisfaction rates could be attributed to the near-instant relief of the fasciotomy while conservative-treated patients had to be treated longer for noticeable results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Patients with CECS who had a fasciotomy were satisfied with the surgical therapy and reported better subjective injury status than conservative-treated patients with ERLP. A success rate of 84.4% for fasciotomy in CECS was reported and is in concordance within the range of 78%–98% reported by other studies 3 7 18–20. The difference between fasciotomy and conservative groups in satisfaction rates could be attributed to the near-instant relief of the fasciotomy while conservative-treated patients had to be treated longer for noticeable results.…”
Section: Discussionsupporting
confidence: 89%
“…A relative high number of deep posterior compartment cases responded to our survey (14/38, 36.8% vs 30/110, 27.3% in our total population). This might suggest that the overall success rate of fasciotomy in our hospital is underestimated, compared with other studies with primary focus on the anterior compartment 3 7 18–20…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…One study reported an up to 35 % lat-CECS rate [2]. It is therefore somewhat strange why published results on surgery for this supposedly frequent type of lower leg CECS are scarce [11,13,14,16]. To date, the outcome of isolated CECS of the lateral compartment is reported in just 3 individuals, one with an excellent and 2 with a fair postoperative result [13].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of untreated CECS is often very incapacitating for active individuals and negatively affects quality of life [11,14]. Up to 85 % of CECS patients are unable to practice sports activities at the desired level before surgery [11,21]. The aim of the operation is to facilitate a return to a desired level of sports activity, but success is not always achieved.…”
Section: Discussionmentioning
confidence: 99%